Antiviral therapeutic approaches for human rhinovirus infections - Casanova, Victor (Future Virol, 2018)
Human rhinoviruses are the primary etiological agent of the common cold. This infection can be mild and self-limiting in immunocompetent hosts, but can be associated with bronchiolitis in infants, pneumonia in the immunosuppressed and exacerbations of pre-existing pulmonary conditions such as asthma or chronic obstructive pulmonary disease. Many of these conditions can place significant economic costs upon healthcare infrastructure. There is currently no licensed vaccine for rhinovirus, as the large variety of rhinovirus serotypes has posed significant challenges for research. In this review, we discuss current knowledge around antiviral drugs and small molecule inhibitors of rhinovirus infection, as well as antiviral host defense peptides as exciting prospects to approach the development of novel therapeutics which target human rhinovirus.